FRI0134 Progression of subclinical atherosclerosis over five years in patients with early rheumatoid arthritis. (23rd January 2014) - Södergren, A.; Karp, K.; Boman, K.; Eriksson, C.; Lundström, E.; Smedby, T.; Möller, B.; Rantapää-Dahlqvist, S.; Wållberg-Jonsson, S.
Abstract : Background: Patients with rheumatoid arthritis (RA) have an increased mortality and morbidity due to cardiovascular disease (CVD). Premature atherosclerosis can be measured by ultrasound of intima media thickness (IMT) and of flow-mediated dilation (FMD). In patients with RA of recent onset, we have found IMT and FMD to be similar as in controls at diagnosis. Objectives: In this prospective 5-year follow up, we aimed to investigate for increased progression of atherosclerosis in the patients with early RA compared to the controls. We also aimed to analyze the relationship between IMT and FMD and traditional CVD risk factors as well as markers of inflammation. Methods: Patients from northern Sweden diagnosed with early RA are consecutively recruited into a ongoing prospective study of co-morbidity. From these patients, a subgroup aged ≤60 years (n=71), was consecutively included for measurements of IMT of a. carotis communis and FMD of a. brachialis. The ultrasound measurements were taken at inclusion (T0) and after 5 years (T5). 40 age-sex matched controls were included. The patients were clinically assessed (DAS28, TJC, SJC, DMARDs) and blood was analysed for cholesterol, HDL-cholesterol, triglycerides, ESR and CRP. SCORE and Reynolds Risk Score were calculated at T0 and T5. Results: Patients with RA had a significant aggravation in both IMT (0.52 at T0 and 0.58 at T5, p<0.001) and FMD (109.2% at T0 and 107.0 at T5, p<0.001). In controls the increase was only significant for IMT (0.55 at T0 and 0.60 at T5, p<0.001). In simple linear regression analyses among RA-patients, the IMT at T5 was significantly associated with several variables at T0: systolic blood pressure (BP), cholesterol, triglycerides, SCORE and Reynolds Risk Score. In the corresponding analyses of FMD at T5, it was significantly inversely associated with age, smoking, SCORE as well as Reynolds Risk Score at T0 and area under the curve (AUC) for DAS28 over 60 months. In controls, the IMT at T5 was significantly associated with gender, age, systolic BP, cholesterol, triglycerides, HDL (inversly), BMI and SCORE at T0, whilst FMD was not significantly associated with any of the variables at T0. In a multiple regression model among RA-patients with age, systolic BP, triglycerides, cholesterol, HDL at T0 and AUC for DAS28 over 60 months, IMT at T5 was significantly associated with the BP and cholesterol. In another multiple regression model with age, smoking, cholesterol and AUC for DAS 28 over 60 months, FMD at T5 was significantly associated only with the AUC DAS28. Conclusions: After five years, the increase in subclinical atherosclerosis tended to be more evident among patients with early RA compared to the controls. Both traditional CVD risk factors as well as inflammatory load over time seems to contribute to this increased atherosclerotic findings among patients with RA. Disclosure of Interest: None Declared